2019
DOI: 10.1007/s00259-019-04630-y
|View full text |Cite
|
Sign up to set email alerts
|

Digital versus analogue PET in [68Ga]Ga-PSMA-11 PET/CT for recurrent prostate cancer: a matched-pair comparison

Abstract: Purpose Digital PET/CT scanners represent a significant step forward in molecular imaging. We report here the clinical impact of digital PET in PSMA-PET/CT. Methods In this retrospective study, 88 consecutive patients who underwent [ 68 Ga]Ga-PSMA-11 PET/CT on a digital PET/CT (dPET/CT) scanner for recurrent prostate cancer (PC) were included in a first cohort. In a second step, 88 individuals who underwent an analogue [ 68 Ga]Ga-PSMA-11 PET/CT (aPET/CT) were selected after they were matched to the first cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 32 publications
5
45
0
1
Order By: Relevance
“…In addition, state-of-the-art digital systems often include longer axial coverage, smaller crystals, and more advanced electronics, which lead to higher sensitivity, higher spatial resolution, and shorter deadtime. These improved performance characteristics have been confirmed by a number of publications [1,2], which correspond to improvements in image quality and lesion detection [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, state-of-the-art digital systems often include longer axial coverage, smaller crystals, and more advanced electronics, which lead to higher sensitivity, higher spatial resolution, and shorter deadtime. These improved performance characteristics have been confirmed by a number of publications [1,2], which correspond to improvements in image quality and lesion detection [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 60%
“…As described in the introduction, digital PET/CT represents a step forward in molecular imaging, with increasing numbers of publications confirming the favourable performance characteristics for such scans in comparison to previous-generation analogue systems [ 1 , 16 ], including increased lesion detection and sensitivity [ 1 , 3 , 4 , 13 , 17 ]. Previous authors have reported head-to-head studies comparing digital and analogue systems, showing both improved image quality and upstaging of individuals [ 10 ], as well as improved recovery (as shown by higher SUV values) and lesion sharpness [ 3 , 6 ]. Traditionally, shorter list-mode acquisitions have been associated with decreased lesion detection, as most recently shown for [ 68 Ga]Ga-PSMA-11 PET/CT by Rauscher et al (using an analogue scanner) [ 18 ] with 1 min/bp reconstructions (equivalent to 1/3 rd of the standard) associated with reduced detection of up to 36% of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…1 illustrates, we are still a long way from demonstrating higher lesion counts as proof of a true benefit to patient outcomes. • Spatial resolution and contrast recovery [42,[98][99][100] • Noise/background variability [42,99,100] • Lesion detection [101] Patients Level 1:…”
Section: Prostate Cancermentioning
confidence: 99%
“…Several studies have shown improvements in lesion detection with digital scanners compared to analog systems for 18 F-FDG PET, possibly also leading to higher detectability of UBUs using [ 18 F]-PSMA-1007 [26,27]. This was suggested by Alberts et al, who reported a higher detection rate of both prostate cancer lesions and benign PSMA-avid lesions with digital than with analog systems [28]. It can therefore be assumed that, with more installations of high-end digital PET systems, the frequency of UBU in 18 F-PSMA-1007 imaging will become even more challenging.…”
Section: Discussionmentioning
confidence: 97%